2019
DOI: 10.1177/0301006619825782
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Errors Support the Notion of Masking by Object Substitution

Abstract: Two experiments examined the effect of Object Substitution Masking (OSM) on the perceptual errors in reporting the orientation of a target. In Experiment 1 a four-dot trailing mask was compared with a simultaneous-noise mask. In Experiment 2, the four-dot and noise masks were factorially-varied. Responses were modelled using a mixture regression-model and Bayesianinference to deduce whether the relative impacts of OSM on guessing and precision were the same as those of a noise mask, and thus whether the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Second, two theories assuming object-level interferences between the target and mask are considered: object substitution theory (e.g., Di Lollo et al, 2000 ; Kahan & Lichtman, 2006 ; Pilling et al, 2019 ) and object updating theory (e.g., Goodhew, 2017 ; Lleras & Moore, 2003 ; Pilling & Gellatly, 2010 ). As the differences between these theories are subtle and the present study did not aim to differentiate them, we tentatively consider the object updating theory as a working hypothesis because it imposes looser constraints on the mechanism of common-onset masking compared to the object substitution theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, two theories assuming object-level interferences between the target and mask are considered: object substitution theory (e.g., Di Lollo et al, 2000 ; Kahan & Lichtman, 2006 ; Pilling et al, 2019 ) and object updating theory (e.g., Goodhew, 2017 ; Lleras & Moore, 2003 ; Pilling & Gellatly, 2010 ). As the differences between these theories are subtle and the present study did not aim to differentiate them, we tentatively consider the object updating theory as a working hypothesis because it imposes looser constraints on the mechanism of common-onset masking compared to the object substitution theory.…”
Section: Discussionmentioning
confidence: 99%
“…Based on observations that metacontrast masking peaks at positive SOAs (when the target precedes the mask), several influential models have been proposed (Bachmann, 1984;Breitmeyer & Ganz, 1976;Breitmeyer & Ögmen, 2000). (Bridgeman, 1971;Francis, 1997), a sparse mask-such as four dots-remotely surrounding the target is mainly used in common-onset masking (e.g., Di Filmer, Mattingley, & Dux, 2014;Llears & Moore, 2003;Pilling, Guest, & Andrews, 2019).…”
Section: Introduction Backward Masking As a Tool For Probing Perceptual Microgenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, it is worth noting that some recent studies have claimed to support the object-substitution account, but although this evidence is consistent with the model, it is also consistent with other models—that is, it is not theory-diagnostic. For example, it has been found that OSM operates on an all-or-none rather than a graded perceptual basis (Pilling, Guest, & Andrews, 2019). This could be considered consistent with the object-substitution account, but such a finding is in no way exclusive to the object-substitution account.…”
Section: Discussionmentioning
confidence: 99%